Atomically Smooth Graphene‐Based Hybrid Template for the Epitaxial Growth of Organic Semiconductor Crystals. (21st December 2020) - Nguyen, Nguyen Ngan; Lee, Hyo Chan; Baek, Kangkyun; Yoo, Min Seok; Lee, Hansol; Lim, Hyungsub; Choi, Shinyoung; Kim, Cheol‐Joo; Nam, SungWoo; Cho, Kilwon
Abstract: Atomically thin 2D materials are good templates to grow organic semiconductor thin films with desirable features. However, the 2D materials typically exhibit surface roughness and spatial charge inhomogeneity due to nonuniform doping, which can affect the uniform assembly of organic thin films on the 2D materials. A hybrid template is presented for preparation of highly crystalline small‐molecule organic semiconductor thin film that is fabricated by transferring graphene onto a highly ordered self‐assembled monolayer. This hybrid graphene template has low surface roughness and spatially uniform doping, and it yields highly crystalline fullerene thin films with grain sizes >300 nm, which is the largest reported grain size for C60 thin films on 2D materials. A graphene/fullerene/pentacene phototransistor fabricated directly on the hybrid template has five times higher photoresponsivity than a phototransistor fabricated on a conventional graphene template supported by a SiO2 wafer. Abstract : A hybrid graphene template to grow high‐crystalline C60 thin films is demonstrated by transferring graphene onto a highly ordered octadecyltrichlorosilane self‐assembled monolayer (o‐ODTS‐SAM). Spatially uniform charge‐carrier density and low surface roughness of the graphene/o‐ODTS‐SAM template result in the growth of highly crystalline C60 thin films with grain sizes >300 nm.